Analisis Pemahaman Mahasiswa Informatika dalam Menyelesaikan Rute Terpendek Menggunakan Algoritma Dijkstra dengan Graf Berbobot - Jaiman, Fridolin; Fallo, Diana Yanni Ariswati; Banung, Floriana Letni (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The Dijkstra algorithm is one of the shortest path search methods that is widely applied in various fields of computer science, such as digital navigation systems, logistics planning, and computer network optimization. In the context of informatics education, these algorithms are taught to reinforce programming logic and understanding of the structure of weighted graphs. However, the implementation of learning in higher education still faces various challenges, especially the understanding of informatic education students in solving the shortest path problems using the Dijkstra algorithm, as well as developing a learning approach based on case studies ans simulation. The method used is aused is a deskriptive qualitative approcah with data collection techniques in the form of learning obsevations, analysis of student assignment documents, and open questionnaires. The results showed that most students understood the process of initialization and tracing the minimum weight, but encountered difficulties in selecting the next node and tracking the shortest path. Case studies of weighted graphs and manual visualizations have been shown to help students understand and help students understand algorithmic processes more thoroughly. These findings show that real-life case-based learning models and manual simulations are able to improve students’ analytical skills and understanding of the working mechanisms of the Dijkstra algorithm.